Utilization of Papaya and Pandan Leaf Extract as a Source of Vegetable Pesticides - Vivi D. A. Sangkota; Sitti Rahmawati; Purnama Ningsih; Jamaludin M. Sakung (Jurnal Akademika Kimia, 2022)
In this study, the manufacture of vegetable pesticides using natural ingredients of papaya leaf extract and pandan leaf extract has been carried out as a substitute for synthetic pesticides to kill plant pest organisms (OPT). This research was an experimental study using 250 experimental organisms Larvae of Spodoptera litura which were divided into 5 groups. Each group consisted of 10 larvae of Spodoptera litura. Each group was repeated 5 times. As test materials, papaya leaf extract and pandan leaf were added to the media solution containing the test organisms. The concentration of each extract was different for each treatment in each vial, for P1 (Papaya Leaf) which was 150 ml, P2 (Pandan Leaf) 150 ml, and P3 300 ml (Mixture of Papaya Leaves and Pandan Leaves), and Control was 0ml. Data were obtained by counting the number of larvae that died on the first day after application. Based on the data, the percentage value of larval mortality was calculated using the Percentage formula, while the percentage value of larval mortality in the control treatment was calculated using the Abbott formula, the average value of mortality for each replication was calculated using the Datum formula. Based on the testing of vegetable pesticides from papaya leaf extract and pandan leaf extract, the characteristics of vegetable pesticide products from papaya leaf extract and pandan leaf extract were obtained, with the highest mortality percentage obtained in P3 treatment (a mixture of papaya leaf extract and pandan leaf extract) of 88%, while the percentage of mortality was 88%. in treatment P1 (pawpaw leaves) by 70%, and the percentage value of death in treatment P2 (pandan leaves) by 38%. From these results, papaya leaves and pandan leaves are effectively used as sources of environmentally friendly vegetable pesticides in killing plant pests of Spodoptera litura larvae.